Radiolabeling of cidofovir with technetium-99m and biodistribution studies - Raquel Gregorio Arribada; Nara Caroline Pereira; Valbert Nascimento Cardoso; Armando da Silva Cunha Júnior; André Luís Branco de Barros (Universidade de São Paulo, 2020)
Radiolabeling cidofovir with technetium-99m (99mTc-CDV) is an innovative procedure that enables real-time monitoring of the drug. Essays were performed in vitro, showing high radiolabel stability within 24 h. Blood clearance, biodistribution studies, and scintigraphic images were performed in healthy mice in order to evaluate the profile of the drug in vivo. 99mTc-CDV showed biphasic blood circulation time and significant kidney uptake, indicating that 99mTc-CDV is preferentially eliminated by the renal route. Bones also showed important uptake throughout the experiment. In summary, cidofovir was successfully labeled with technetium-99m and might be used in further studies to track the drug.